Anxiety-depressive spectrum disorders in patients with obstetric antiphospholipid syndrome - A. B. Borisova; D. Yu. Veltishchev; T. M. Reshetnyak; T. A. Lisitsyna; E. L. Nasonov (Научно-практическая ревматология)
The aim – to determine the frequency and characteristics of anxiety-depressive spectrum disorders (ADSD) in patients with obstetric antiphospholipid syndrome (APS).Material and methods. The study is prospective-retrospective. Data on obstetric pathology was obtained from medical documents and from conversation with a patient. Stress factors were assessed upon inclusion in the study. Diagnosis of ADSD was carried out by a psychiatrist, according to ICD-10. The study included 61 women with APS, established according to the international criteria of 2006, who had a history of pregnancy. 30 (49.2%) of 61 patients had pregnancy loss (PL). Systemic lupus erythematosus (SLE) was diagnosed in 29 (47.5%) women. The average age of patients at the time of inclusion in the study was 40.9±11.0 years: 41.2±7.77 years in patients with PL and 40.7±12.8 years in patients without PL.Results. ADSD were identified in the majority of women with APS – 53 (86.9%) out of 61. These mental disorders developed in the majority of patients before the onset of APS (37 (69.8%) out of 53). Moderate and severe depression in patients with PL was more related to stressful events not associated with APS (mainly with childhood and adolescent psychological trauma), and was also more often detected in the presence of PL after the week 10 of gestation and more than two PL. Childlessness as a stress factor at the time of the study was significant for 7 (38,9%) out of 18 patients with PL who did not have children. Almost half (14 (46.7%) out of 30) of patients with PL had more than two interrupted pregnancies (multiple PL). In the group of patients with multiple PLs, significantly more often than in patients with one or two PLs, a pronounced distortion of logical thinking was detected, while the frequency of organic-type thinking disorders associated with ischemic damage to the central nervous system within the framework of APS did not differ in patients in the compared groups.Conclusion. The incidence of depression in women with APS did not depend on a history of PL. Multiple PLs predisposed to more severe types of depression. The psychopathological features of ADSD in patients with multiple PLs were determined – more frequent pronounced distortions of logical thinking. It has been established that childlessness is not a significant stress factor for all patients.